Critical criminology in South Africa : developing paradigms and theoretical models - Rossouw, Gideon (Institute of Criminology, 2021)
The unmasking of apartheid and the unmasking of the state run together in an analysis of the legacy of social engineering. The integration of macro and micro levels of analysis offer a complex challenge to social theorists, and this in conjunction with the demands of analysing a racially divided society undergoing extreme forms of crisis and change, require a sophisticated· level of theorizing which is informed by the practical experiences which constitute the social relations of the society. The perspectives that can be offered in the fields of crime, crime control and the social consequences of economic and social interaction cannot be complete without considering the political framework within which the competing demands for power, influence and wealth are taking place. These structures have undergone radical ideological transformations in the recent past, which have been linked to the radical consequences of the end of the ·cold War' and the apparent era of demilitarising international relations between powerful states. The issues which will cloud the judgements made in the field of Criminology are linked to these broader matters of international relations, and gee-political issues, because the political struggle in South Africa has been utilized in terms of this debate, and the achievement of the democratic demands has become foreseeable and realistic because of changes taking place at international level.